2009
DOI: 10.1007/s10517-009-0629-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Orosomucoid in the Regulation of Plasma Proteolytic Systems during Experimental Renal Failure

Abstract: Activity of plasma proteolytic systems was studied in outbred albino rats with acute renal failure. The possibility of treating this disorder with acute phase protein alpha-1-acid glycoprotein was evaluated. Acute renal failure was induced by single subcutaneous injection of mercury chloride (II). The parameters were evaluated on day 5 postinjection. alpha-1-Acid glycoprotein in a dose of 150 mg/kg was administered 3 times. Acute renal failure was accompanied by activation of the complement system and fibrin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…Orosomucoid, being an acute phase protein, contributes to immune response in inflammatory states modulating chemotaxis of neutrophils, superoxide generation and aggregation [46]. On the other hand, a recent study in a murine model of acute renal failure has shown that orosomucoid partially restored activity of clotting and complement systems in acute renal failure [47]. This effect may be due to accumulation of orosomucoid in renal tissue and its protective action in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Orosomucoid, being an acute phase protein, contributes to immune response in inflammatory states modulating chemotaxis of neutrophils, superoxide generation and aggregation [46]. On the other hand, a recent study in a murine model of acute renal failure has shown that orosomucoid partially restored activity of clotting and complement systems in acute renal failure [47]. This effect may be due to accumulation of orosomucoid in renal tissue and its protective action in situ.…”
Section: Discussionmentioning
confidence: 99%
“…После удаления камня и вос-становления проходимости мочевыводящих путей используются различные консерватив-ные терапевтические подходы при МКБ. Учи-тывая роль оксидативного стресса и факторов иммунной системы в патогенезе калькулезно-го пиелонефрита и его осложнений, целесооб-разным является включение в комплексную терапию препаратов антиоксидантного и им-муномодулирующего действия [4,[7][8][9][10][11][12][13][14]. Среди последних интерес вызывает синтетический дипептид γ-D-глутамил-L-триптофан натрие-вая соль -«Бестим», который успешно при-меняется при различных инфекционных и ал-лергических заболеваниях, в том числе при пиелонефрите.…”
unclassified
“…Treatment with erythropoietin led to partial recovery of fi brin formation and fi brinolysis. Under analytical in vitro conditions, 30-min incubation of whole blood from healthy donors with erythropoietin in doses of 1.9-30.0 U/liter was followed by a dose-dependent inhibition of the fi brin formation system and activation of fi brinolysis.Dysregulation of plasma proteolytic systems of fi brin formation and fi brinolysis and the anticoagulant system can serve as a key pathogenetic factor for thrombohemorrhagic complications in renal failure of different genesis [4,13]. Erythropoietin (EPO) is a glycoprotein (molecular weight 30.4 kDa) responsible for proliferation, differentiation, and inhibition of apoptosis in glycoprotein-sensitivebone marrow erythroid lineage cells.…”
mentioning
confidence: 99%
“…Dysregulation of plasma proteolytic systems of fi brin formation and fi brinolysis and the anticoagulant system can serve as a key pathogenetic factor for thrombohemorrhagic complications in renal failure of different genesis [4,13]. Erythropoietin (EPO) is a glycoprotein (molecular weight 30.4 kDa) responsible for proliferation, differentiation, and inhibition of apoptosis in glycoprotein-sensitivebone marrow erythroid lineage cells.…”
mentioning
confidence: 99%